Is the Gig Economy a Stepping Stone for Refugees? Evidence from Administrative Data - Felix Degenhardt; Jan Sebastian Nimczik (Institute of Labor Economics (IZA), 2025)
We examine whether gig jobs in online food delivery (OFD) are a stepping stone for refugees entering the Austrian labor market. Our identification strategy combines the quasi-random assignment of refugees to Austrian regions with the expansion of gig firms across the country. The local availability of OFD jobs at the time of access to the labor market initially accelerates job finding among refugees. Subsequently, however, gig workers remain in low-paid, unstable jobs with low career prospects, while the employment rate of refugees without gig opportunities catches up. The local availability of gig jobs negatively affects human capital investments and job search behavior, even among refugees outside the gig economy.
Keywords: J15; J61; J81; 330; employment restrictions; refugees; gig work; labor market integration